Experiences of the Yayasan Pendidikan Islam (Yapis) di Tanah Papua in Extending Human Resources - Helmawati; Rudihartono Ismail (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
The territory of Papua has many obstacles for transportation and human resource development for indigenous Papuan. In this situation, Yayasan Pendidikan Islam (Yapis) di Tanah Papua emerges as one of institutions committed in helping the people and government in Tanah Papua to improve the quality of human resources intensively. Yapis has contributed significantly to improve quality of human resources is 198 educational institutions have spread from basic education to higher education in Tanah Papua. This research was carried out with a qualitative design with a case study format. Information containing data and facts was obtained through interviews, observations, and documentation studies from main sources, such as Yapis administrators, managers of educational institutions (UPT) under Yapis, students, and stakeholders. Analysis of the validity of the information obtained in this paper using the data cross-check method. The results show that Yapis's strategic planning in the development of human resources in Tanah Papua includes the decision on policies regarding the establishment and development of UPTs under Yapis, planning for the availability of human resources, attractiveness of educational facilities and infrastructure to the existence of extra-curricular activities (extracurricular), cadre and fulfilment the welfare of Yapis human resources optimally.